An efficient self-configurable driver for color light emitting diode - Shaheer Shaida, Durrani (2021)
To arrange an accurate load current for the different sets of color LEDs, an efficient LED driver must facilitate the current sharing among the LED strings using a constant current source. Effective utilization of power in an LED string is vital for display panels as it defines the magnitude of the undesirable phenomenon of flickering switching. An efficient and dimmable LED driver suitable for LED back-light drivers in the LED display panel is presented in this thesis. This thesis proposed a color LEDs driver with a self-configuration of the enhanced current mirror in multiple LED strings. In this proposed work, the load currents have been efficiently balanced among the identical and unequal loads of color LEDs. In a traditional current mirror, the buck converter is linked with a fixed current load. Nonetheless, in the proposed improved self-adjustable current mirror, the variation of LEDs load string could be addressed using a single buck converter. The improvement is based on the combinational circuits of transistor and op-amp with proper scheme biasing. The improved dimming circuit is then proposed for exploiting the range of dimming at the string and module level. Furthermore, the proposed current-balancing circuits excluded a separate power supply to control current in different load strings of LEDs (red/green/blue). Since the approach circuit is identical and modular, it could be scaled to any number of parallel current sources. The different bi-level pulsating driving have been performed to reduce the loss while running the LEDs at the high peak current. It is to create two driving parameters, which are the low/high current levels (pulse width modulation) and associated duty cycles, in having the capability to control luminosity effectively. It can be seen, the previous techniques had improved the luminous efficacy of LEDs by using n-level driving techniques but at the trade-off of losing efficiency with the introduction of resistors (variables in series) to create a bi-level phenomenon for the driver. Therefore, this thesis proposes to replace the resistors with the new approach dimming circuit to get a significant improvement in the overall system’s efficiency that can assist to dim an individual LEDs string based on designated color (red or green or blue) LEDs. Meanwhile, in improving illuminance through dimming, the hybridization of pulse width modulated (PWM) and amplitude modulated (AM) has been proposed. As a result, the proposed LEDs driver has shown effective current balancing through the color LEDs string with exploiting a large dimming range. The illumination analysis has also shown a significantly higher when compared with PWM (bi-level pulsating). The computation efficiency for red, green, and blue LEDs strings around range 92% to 99%.